2020
DOI: 10.1371/journal.pone.0242431
|View full text |Cite
|
Sign up to set email alerts
|

Association between alanine aminotransferase within the normal range and all-cause and cause-specific mortality: A nationwide cohort study

Abstract: Background and aim We sought to determine the association between alanine aminotransferase (ALT) in the normal range and mortality in the absence of liver dysfunction to better understand ALT’s clinical significance beyond liver injury and inflammation. Methods A cohort of 2,708 male and 3,461 female adults aged 20–75 years without liver dysfunction (ALT<30 in males & <19 in females, negative viral serologies, negative ultrasound-based steatosis, no excess alcohol consumption) from the National Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
5
13
0
Order By: Relevance
“…However, the contribution of serum AST to mortality was lower (the tenth greatest contributor) than those of other parameters, including serum ALT activity alone (seventh greatest contributor) in the present AI analysis (Table 2). Although many studies have shown associations between low serum ALT activity and mortality [1][2][3][4][5][6]9,11,12], few have shown that high serum AST activity is a risk factor for mortality [18,19]. Therefore, the present findings are consistent with those of the majority of the previous studies concerning serum ALT and AST.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the contribution of serum AST to mortality was lower (the tenth greatest contributor) than those of other parameters, including serum ALT activity alone (seventh greatest contributor) in the present AI analysis (Table 2). Although many studies have shown associations between low serum ALT activity and mortality [1][2][3][4][5][6]9,11,12], few have shown that high serum AST activity is a risk factor for mortality [18,19]. Therefore, the present findings are consistent with those of the majority of the previous studies concerning serum ALT and AST.…”
Section: Discussionsupporting
confidence: 92%
“…As also shown in previous studies [1][2][3][4][5][6]9,11,12], we found that people with low serum ALT activity are at a higher risk of mortality. However, the ranges of serum ALT activity that made positive and negative contributions to mortality overlapped (Figure 1 and Figure 3), which may have reduced the overall contribution calculated for serum ALT activity in the present study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…ALT, and gamma glutamyl transferase [GGT]), and similar associations were found for non-liver disease mortality. 10 Elevated serum ALT within the normal range is initially associated with lower mortality, 11 although this effect is not observed at ≥17 U/L. Older adult populations tend to exhibit significantly less mortality with elevated ALT levels than do younger populations.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, significantly depleted ALT within normal range at the time of diagnosis is an independent risk factor contributing to increased mortality in elderly adults who have suffered an ischemic stroke 14 and those with stable coronary heart disease 15,16 . Some researchers have reported a positive association between the ALT, even within normal range, and mortality from liver disease, 17 although with inconsistent directions and magnitudes, which can be attributed to the varying ranges of ALT levels that were examined, inclusion of confounders, and differences in study populations 11 …”
Section: Introductionmentioning
confidence: 99%